Integrasi Ekologis Antara Ternak Sapi Dengan Pengelolaan Tanaman Jagung Yang Ditumpangsarikan Dengan Tanaman Kacang-Kacangan Di Lahan Kering: Ecological Integration Between Cattle with the Management of Corn Intercropped with Legumes on Dry Land - I Ketut Ngawit (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
The obstacle to rearing cattle with a herding system on dry land is the unstable availability of feed because the potential for forage production is low. The reason is because dry land is not managed intensively. The research was conducted with the aim of evaluating the application of a monocrop cropping pattern system and intercropping between corn and beans in dry land. The experiment was designed with a randomized block design consisting of nine treatments, namely monocrops of corn, peanuts, soybeans, red beans and cowpeas, as well as intercropping between corn and peanuts, soybeans, red beans and cowpeas. The results of the research show that in the management of a monocrop cropping system and intercropping between corn and beans, weed diversity was found to be quite high, namely 20 families with 39 species, which included 10 species of Poaceae, 9 species of sedges and 20 species of broadleaf. The characteristics of the weeds found were high in species diversity, the ability to spread evenly throughout the corn and bean planting area was high and the ability to dominate the planting area was also high. The best quantity and quality of forage products as raw materials for animal feed are obtained from moorland management with monocrop planting patterns and intercropping of corn with peanuts and cowpeas. In this moorland management system, the potential for forage products obtained is 10.81 – 13.60 kw ha-1 day-1 and the potential land capacity for raising cattle is 5.21 – 5.53 ST ha-1.